The Role of miR-155 in Myeloid cells during Experimental Autoimmune Encephalomyelitis - LYONS, VICTORIA (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2020)
Multiple Sclerosis (MS) is a chronic autoimmune disease of the central nervous system (CNS) characterised by multifocal demyelinating lesions with associated neuronal damage. Although MS is a CD4+ T cell-mediated disease, myeloid cells, including microglia and monocyte-derived macrophages, have recently garnered significant attention for their dual role in both sustaining chronic neuroinflammation and promoting tissue repair. Understanding the molecular mechanisms that regulate the plasticity of these cells is essential to exploiting their regenerative abilities in a therapeutic setting. The microRNA (miRNA) miR-155 has a known role in regulating macrophage plasticity through promoting a proinflammatory polarisation state, however its exact role in MS or its animal model is not yet fully elucidated. The aim of this project is to investigate the role of miR-155 in an animal model of MS and determine whether miR-155 deletion in macrophages skew their polarisation towards an anti-inflammatory phenotype with reparative abilities. Experimental Autoimmune Encephalomyelitis (EAE) is a well-established murine model of MS used to investigate immunopathological mechanisms of disease. Findings from this research project using wild type (WT) EAE mice revealed an induction of miR-155 in myeloid cells, in particular macrophages, within the CNS. Importantly, miR-155 induction correlated with expression of inflammatory genes during the clinical onset of disease, suggesting miR-155 is required for polarisation towards a proinflammatory tissue-destructive phenotype. To confirm miR-155 is required for proinflammatory polarisation of macrophages, novel miR-155fl/fl x LysMCre mice were generated where miR-155 was deleted in immune cells of the myeloid lineage. In vitro studies using two separate macrophage populations, bone marrow derived macrophages (BMDMs) and peritoneal macrophages, established that miR-155 deletion attenuated expression of the proinflammatory marker, iNOS, whilst promoting anti-inflammatory genes, such as ARG1 and ARG2. Collectively, in vitro findings indicated miR-155 deletion promoted macrophages exhibiting an anti-inflammatory phenotype. v The importance of miR-155 in myeloid cells during EAE was highlighted when miR-155fl/fl x LysMCre mice immunised with a reduced rMOG dose resulted in a delayed onset of clinical scores, reduced disease severity, atypical EAE, or in some cases disease resistance. Histological analysis of miR-155fl/fl x LysMCre spinal cords revealed immune cell accumulation surrounding the meninges with attenuated parenchymal infiltration, with infiltrating macrophages and activate microglia appearing to co-express iNOS and ARG1 at sites of spinal cord inflammation. Collectively, in vivo studies supported the potential of ameliorating EAE severity through deleting miR-155 from myeloid cells. Overall, data generated in this research project supports a role for miR-155 in regulating macrophage plasticity by promoting a proinflammatory phenotype associated with CNS demyelination. Targeting miR-155 may therefore provide a novel strategy to promote CNS repair through harnessing reparative capabilities of macrophages.
APPROVED
Keywords: Multiple Sclerosis; Autoimmune disease; miR-155; Myeloid cells